Pengaruh Laju Alir Substrat Terhadap Konsentrasi Sel pada Fermentasi Reject Nanas Menjadi Bioetanol Secara Kontinu - Rendy Hidayat; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is a renewable alternative energy sources that can be used as an alternative fuel. A substance that potential as bioethanol feedstock is rejected pineapple, which it was wasted of pineapple plantation that never be used optimally. Glucose content of rejected pineapple can be converted into bioethanol through fermentation process. This research aimed to determine the effect of cells concentration on bioethanol conversion with substrates flow rate variation of rejected pineapple fermentation into bioethanol, determine the substrate flow rate influences of cell concentration, and determine the optimum residence time of rejected pineapple continuous fermentation process. Fixed variable used is 5 liters of holding capacity, 4.5 of pH, 0.3% contents of inoculum, 0.5% contents of urea, 0.08% contents of phosphorus and room temperature used as fermentation temperature. Varied variables is the variation of feed flow rate: 5 L / day; 2.5 L / day; 1.67 L / day; 1:25 L / day and 1L / day. Research procedures include pretreatment, inoculation, fermentation and purification using a vacuum evaporator. Analysis performed into cell concentration and ethanol concentration analysis. The results showed that the optimum flow rate was 2.5 L / day with the of ethanol 7% contents and 17.1 g / L of cells concentrationKeyword: Bioethanol, continuous, cells concentration, Saccharomyces cereviceae